Driving Consumer Value Co-creation and Purchase Intention by Social Media Advertising Value - Hussain, Ali; Ting, Ding Hooi; Mazhar, Muhammad (Frontiers in Psychology, 2022)
Social media advertisement (ad) is a growing phenomenon designed to engage customers’ attitudes. However, despite their continued adoption, little remains known regarding the effectiveness of social media advertisement to co-create brand value. In response to this gap, the present study aims to deepen the theoretical understanding of consumer value co-creation through social media advertising value. The data was collected using purposive sampling from 286 experienced social-media users, and the model was tested using partial least square (PLS)-based structural equation modelling. The results indicate that entertainment, aesthetic appeal, interactivity, and trendiness significantly affect the adverting value of social media ads. In turn, advertisement value affects consumers’ intention for value co-creation. Consequently, our findings suggest the importance of social media advertising value where marketers may enhance the consumer-brand engagement by incorporating interesting content, which may encourage the customer's interaction with the social media ads and leading to the strengthening of value co-creation behavior. The results further contribute to nascent marketing literature by demonstrating that value co-creation acts as an antecedent to generating positive electronic word-of-mouth (e-WOM) on social media platforms to drive consumers’ online brand purchase intention.